2020
DOI: 10.1111/acfi.12712
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of corporate social disclosures of the apparel industry following crisis: an institutional approach

Abstract: This study explores how the social and environmental information disclosed by organisations following a crisis is influenced by the institutional environment. Through content analysis, the study examines disclosures of apparel industry organisations after the Rana Plaza building collapse in Bangladesh. The study finds that the accountability demonstrated by global apparel buyers following a crisis is attributable to Western cultural expectations and norms, legitimacy concerns and global constituent pressures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 79 publications
0
30
0
Order By: Relevance
“…Consequently, the candidates gain instruction to signal their quality and reduce information irregularities Useful for describing behavior when two parties (individuals or organizations) have access to different information (Leung and Snell, 2021;Charumathi and Ramesh, 2020) Institutional theory (Meyer and Rowan, 1977) Organizations reflecting institutionalized environments maintain gaps between their formal structures and their ongoing work activities Properties are appropriately assigned, and confirmed that those persons with fewer financial properties are protected. They also encourage belief by providing monitoring and justice systems which follow to a public set of rules (Akbar and Deegan, 2021;Bellamy et al, 2020) Neo-institutional theory (Meyer and Rowan, 1977;DiMaggio and Powell, 1983) Neo-institutional theory provides a suitable conceptual narrative for understanding the context of corporate voluntary disclosure. Neo-institutional theory fundamentally argues for the need of firms to align extant organizational practices with institutionalized norms and structures in a given organizational field Neo-institutional theory highlights on three evaluates (1) institutes in the society, (2) governance instrument and (3) actors (Alshbili and Elamer, 2020;Shahab and Ye, 2018) Impression management theory (Goffman, 1959) Impression management is the effort to control or influence other people's perceptions There are two main motives for trying to manage the impressions of others: instrumental and expressive.…”
Section: Source(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the candidates gain instruction to signal their quality and reduce information irregularities Useful for describing behavior when two parties (individuals or organizations) have access to different information (Leung and Snell, 2021;Charumathi and Ramesh, 2020) Institutional theory (Meyer and Rowan, 1977) Organizations reflecting institutionalized environments maintain gaps between their formal structures and their ongoing work activities Properties are appropriately assigned, and confirmed that those persons with fewer financial properties are protected. They also encourage belief by providing monitoring and justice systems which follow to a public set of rules (Akbar and Deegan, 2021;Bellamy et al, 2020) Neo-institutional theory (Meyer and Rowan, 1977;DiMaggio and Powell, 1983) Neo-institutional theory provides a suitable conceptual narrative for understanding the context of corporate voluntary disclosure. Neo-institutional theory fundamentally argues for the need of firms to align extant organizational practices with institutionalized norms and structures in a given organizational field Neo-institutional theory highlights on three evaluates (1) institutes in the society, (2) governance instrument and (3) actors (Alshbili and Elamer, 2020;Shahab and Ye, 2018) Impression management theory (Goffman, 1959) Impression management is the effort to control or influence other people's perceptions There are two main motives for trying to manage the impressions of others: instrumental and expressive.…”
Section: Source(s)mentioning
confidence: 99%
“…These contextualized features are frequently associated with different kinds of corporation features in different states and capital markets. Several theories have been applied in the literature to significantly disclose voluntary information in the organizations such as agency theory (Pakawaru et al, 2021;Nguyen et al, 2021;Zaid et al, 2020;Biswas et al, 2019;Katmon et al, 2019;El-Diftar et al, 2017), signaling theory (Leung and Snell, 2021;Charumathi and Ramesh, 2020), resource dependence theory (Khan et al, 2021), impression management theory (Morales-Raya et al, 2019), stakeholder theory (Singh and Chakraborty, 2021;Charumathi and Ramesh, 2020;Rashid et al, 2020;Buallay et al, 2020;Waheed and Yang, 2019;Dias et al, 2019;Hu et al, 2018), political economy theory (Agyei and Yankey, 2019), legitimacy theory (Acar and Temiz, 2020;Hickman, 2020;Pitrakkos and Maroun, 2020;Rosa Portella and Borba, 2020;Al Fadli et al, 2019;Ullah et al, 2019;Garas and EIMassah, 2018;Sobhan et al, 2018;William et al, 2018), institutional theory (Akbar and Deegan, 2021;Bellamy et al, 2020;Oliveira et al, 2019;Russo-Spena et al, 2018) and neo-institutional theory (Kilincarslan et al, 2020;Alshbili and Elamer, 2020;Sekhon and Kathuria, 2020;Shahab and Ye, 2018).This variation findings of the earlier literature demands that need for an inclusive review of the theories in CVD works.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the linkage between “accountability” and “legitimacy”, conceptually better performance and disclosure demonstrate accountability and help secure legitimacy. While accountability is an important means to develop, manage, maintain and restore legitimacy (Birkey et al , 2016; Hyndman and McConville, 2018; Kim, 2019; Kuruppu et al , 2019), non-financial disclosures have been criticised to reflect impression management rather than genuine demonstration of accountability and commitment to sustainability (Adler et al , 2018; Akbar and Deegan, 2021; Cho et al , 2015a; Kuruppu et al , 2019; Melloni et al , 2017). Such concerns are echoed by papers included in this special issue, with Abhayawansa and Adams (2022) finding a lack of information on pandemic risk and a short-term focus on climate risk, and Hadro et al (2022) reporting a mismatch between information disclosed and information of interest to stakeholders.…”
Section: Development Of the Eeri Frameworkmentioning
confidence: 99%
“…Stakeholders value the quantitative information more than the qualitative one and can positively influence bank risk-taking [ 30 ]. Additionally, website disclosures are a timely disclosure medium and rich form of communication available to a broad range of stakeholder groups [ 31 ]. Therefore, the sensitive response of the stakeholders to the negative disclosures can also trigger runs on an inefficient bank [ 32 ] and can lower the distance to default [ 33 ].…”
Section: Literature Reviewmentioning
confidence: 99%